Kartli - the center of Georgia, Gathering and uniting the Georgians - Topchishvili, Roland (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2019)
The Georgian ethnic unit consisted of various territorial units. These local units had their original names. The abundance of territorial units was caused by geographical factors. Over time, the same geographical factor led to the unification of Georgians, which also led to their aspiration for a united state organization. As a result of this aspiration, a common name ‘Kartveli’- Georgian was produced, and then we got the name of the country „Sakartvelo“ - Georgia from this ethnonym. It occurred because one of the territorial units of Georgia, called Kartli, was located amid Georgia. Along with this factor, the landscape and natural geographical environment had determinant importance. The physical geography of almost every historical - ethnographic part of Georgia was diverse. They differed from each other in elevation, deep and relatively shallow valleys, sloping mountains, forest cover, the number of arable lands, protection, and terms of sunlight. The landscape and natural-geographic environment of Georgia created unique and different economic forms. None of the territorial units could exist independently- they complemented each other in this respect; what one had didn’t have the other. Mutual compatibility was the consequence of the history of Georgia and the Georgian nation. The historical and ethnographic parts of Georgia were in a close economic union with each other which was a basis for the consolidation of the Georgian people. Consolidation was taking place around Kartli. Kartli was the shortest route to Southern Georgia. Different historical and ethnographic parts of Georgia were linked to each other with Kartli. The population of Kartli, due to an exogenous factor, is often used to reach a critical threshold. In this case, the rescuers of Kartli were those territorial units where the enemy could not be included. As a result of the migration of the increasing population of the highlands and western Georgia – the population in Kartli was reproduced. Thus, Kartli was not only a region in the center of Georgia but also the region gathering and uniting Georgians. The natural geographic and landscape factors, in turn, led to the formation of the Georgian ethnic unit as a nation, the formation of the Georgian literary and theological language, and the existence of the capital in Kartli.